Peer review of the pesticide risk assessment of the active substance phosphine - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Spain and co‐rapporteur Member State Germany for the pesticide active substance phosphine are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of phosphine as a post‐harvest indoor insecticide to control insects infesting stored grains (barley, oat, rye, wheat), cacao and coffee beans, tree nuts and oilseeds and dried fruit via gassing application (gas‐tight rooms/container). The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.